STEM odaklı matematik öğretiminin özel yetenekli öğrencilerin matematiğe yönelik inançlarına ve stem mesleklerine olan ilgilerine etkisinin incelenmesi - Metin, Ufuk (My University, 2024)
Bu araştırmanın amacı STEM odaklı matematik öğretiminin özel yetenekli öğrencilerin matematiğe yönelik inançlarına ve STEM mesleklerine olan ilgilerine etkisini incelemektir. Özel yetenekli öğrenciler için farklılaştırılmış ve zenginleştirilmiş etkinlere uygun bir sistem olan STEM eğitimi öğrencilerin potansiyellerini daha verimli kullanabilecekleri bir ortam sağlaması önemlidir. Araştırmanın yöntemi nicel olup deneysel desen kullanılmıştır. 2022-2023 Eğitim öğretim yılında İstanbul’da Bilim ve Sanat Merkezine devam eden Bireysel Yeteneklerin Farkettirilmesi (BYF-1) Grubundaki 16 öğrenci Çalışma grubunu oluşturmuştur. 8 Öğrenci deney grubunda 8 öğrenci de kontrol grubunda yer almıştır. Deney grubuna sekiz hafta boyunca STEM odaklı matematik öğretimi uygulanırken kontrol grubuna yürürlükteki Bilsem Öğretim uygulanmıştır. Nicel verileri toplamak için Matematik İnancı Ölçeği, ve FeTeMM Mesleklerine Yönelik İlgi Ölçeği, kullanılmıştır. Matematik İnancı Ölçeği; Faydalılık (9 madde), Kaygı (7 madde), Çaba (4 madde) ve Sınırlılık (4 madde) alt boyutlarından, FeTeMM Mesleklerine Yönelik İlgi Ölçeği fen (10 madde), teknoloji (10 madde), mühendislik (10 madde) ve matematik (10 madde) alt boyutlarından oluşmaktadır. Bu alt boyutlarda ele alınarak nicel verilerin analizleri yapılmıştır. Analizlerde Wilcoxon İşaretli Sıralar Testi ve Mann Whitney U testi kullanılarak öntest-sontest puanları arasındaki farklar değerlendirilmiştir. Araştırma sonucunda, STEM odaklı matematik öğretimi uygulanan deney grubu ile kontrol grubu arasında matematik inancına ilişkin öntest-sontest puanları arasında istatistiksel olarak anlamlı bir fark bulunamamıştır. Ayrıca, matematik inancının faydalılık, kaygı, çaba ve sınırlılık alt boyutlarında da anlamlı bir fark saptanamamıştır. Deney ve kontrol gruplarının öntest-sontest STEM mesleklerine olan ilgi puanları arasında anlamlı bir fark bulunamamıştır. Ayrıca ölçeğin fen, teknoloji, mühendislik ve matematik alt boyutları öntest-sontest puanları arasında da anlamlı bir fark olmadığı görülmüştür. Sonuç olarak; STEM odaklı matematik öğretiminin, öğrencilerin matematik inancı ve STEM mesleklerine olan ilgilerine etkisi olmadığı tespit edilmiştir.

The purpose of this research is to examine the impact of STEM-focused mathematics instruction on the beliefs about mathematics and interest in STEM professions of gifted students. STEM education, which is a system suitable for differentiated and enriched activities for gifted students, is important in providing an environment where students can more efficiently utilize their potentials. The method of the research is quantitative, and an experimental design is employed. A total of 16 students attending the Individual Talent Recognition (BYF-1) Group at the Science and Art Center in Istanbul during the 2022-2023 academic year constitute the study group. Eight students are in the experimental group, and eight students are in the control group. While STEM-focused mathematics instruction is applied to the experimental group for eight weeks, the existing Bilsem Instruction Program is implemented for the control group. Quantitative data is collected using the Mathematics Belief Scale and the Interest Scale in STEM Professions. The Mathematics Belief Scale consists of sub-dimensions of Utility (9 items), Anxiety (7 items), Effort (4 items), and Limitation (4 items). The Interest Scale in STEM Professions includes sub-dimensions related to science(10 items), technology(10 items), engineering(10 items), and mathematics(10 items). Analyses of quantitative data are conducted by addressing these sub-dimensions. Wilcoxon Signed-Rank Test and Mann-Whitney U test are used to evaluate differences between pre-test and post-test scores. As a result of the research, no statistically significant difference was found in pre-test and post-test scores related to mathematics belief between the experimental group receiving STEM-focused mathematics instruction and the control group. Additionally, no significant difference was detected in the sub-dimensions of utility, anxiety, effort, and limitation of mathematics belief. There was no significant difference in the pre-test and post-test interest scores in STEM professions between the experimental and control groups. Furthermore, there was no significant difference observed in the sub-dimensions of science, technology, engineering, and mathematics in the pre-test and post-test scores. In conclusion, it was determined that STEM-focused mathematics instruction did not have an impact on students' beliefs about mathematics and their interest in STEM professions.
Investigation on the effect of stem focused mathematics teaching on gifted students' beliefs towards mathematics and their interest in stem career
Keywords: Belief Towards Mathematics; Bilim; Gifted Student; Matematik; Matematik İnancı; Mathematics; Öğrenim ve öğretim; Özel Yetenekli Öğrenci STEM; Science; STEM; STEM Career Interest; STEM education; STEM eğitimi; STEM Focused Mathematic Teaching; STEM Mesleklerine İlgi; STEM Odaklı Matematik Öğretimi; Study and teaching